Work-Life Balance of Bank Employees during the Pandemic: An Exploratory Analysis - Jain, Bandana Kumari (Tribhuvan University Journal, 2022)
The study attempts to explore the factors of work-life balance (WLB)amid the pandemic and the effects of these derived factors on the overall perception of WLB of bank employees. The quantitative research method was harnessed to explore the objectives. Employees of commercial banks serving in the Morang district, one of the 77 administrative units of Nepal, during the pandemic were the population of the study. Primary data were collected using structured questionnaires. Snowball and purposive sampling methods were implied to get the sample of 193 bank employees. The study extracted four factors; personal demand, family demand, work demand, and social demand dimensions of WLB duringCovid-19. And personal demand factor of WLB stood as the most significant out of the other two significant factors namely family and work demand factors to influence the overall perception of WLB amidst the pandemic. Employees’ self-care and self-development needs are to be incorporated while formulating policies of the organization and more specifically WLB during the traumatic conditions.